Reference Interval for Cystatin C in a Sample of Adult Cuban Population - Dailen Darias Rivera (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Foundation: studying cystatin C has risen interest as it is defined its utility as an early marker and sensitive to chronic renal disease. Determining the range of reference for chemical analysis in clinical laboratories constitutes an essential requirement to implement an adequate quality control program. Objective: to establish the interval of reference of Cystatin C in a sample of adult Cuban population, in the laboratory of the Clinical Surgical Hospital Hermanos Ameijeiras. Method: cross-descriptive study in 249 blood donors (women and men in the same proportion), aged between 18 and 50. By the inmunoturbidimetric method the values of seric cystatin C were obtained and were compared by sex and age group. The interval of reference was calculated and compared with the one proposed by the manufacturer. Results: the interval of reference obtained showed association with sex, but not with the age group. Statistically significant differences were found between the interval of seric reference of cystatin C in both sexes and the one proposed by the manufacturer. Conclusion: the need of counting with values of reference according to each place was evidenced, according to the International Federation of Clinical Chemistry and the standards of clinical laboratory.